1999
DOI: 10.1210/endo.140.1.6405
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Negative Effect of Insulin-Like Growth Factor-I on Growth Hormone Gene Expression in MtT/S Somatotroph Cells

Abstract: Although insulin-like growth factor-I (IGF-I) is shown to have a suppressive effect on GH gene expression at the pituitary level, its molecular mechanism has not yet been clarified. To study the issue, we established a new in vitro system using MtT/S, a recently established rat somatotroph tumor cell line that retains the basic characteristics of somatotroph function. Plasmids containing the GH 5' promoter (approximately 1.75 kb or shorter)-luciferase fusion gene were transfected stably or transiently into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Voss et al (2000) demonstrated that IGF-I decreased endogenous GH mRNA in MtT/S cells, a GH-producing rat pituitary cell line, and this inhibitory effect could not be blocked by inhibitors of phosphatidyl inositol 3 kinase (PI3K) (wortmannin and LY294002) or MAPK (PD098059). In contrast, Niiori- Onishi et al (1999), also using MtT/S cells, reported that IGF-I suppressed luciferase activity driven by a hGH gene promoter, where this action could be blocked by treatment with wortmannin. These divergent results demonstrate that regulation of the endogenous gene vs reporter gene activity may be very different even in the same cell type.…”
Section: Direct Effects Of Igf-i and Insulinmentioning
confidence: 91%
“…Voss et al (2000) demonstrated that IGF-I decreased endogenous GH mRNA in MtT/S cells, a GH-producing rat pituitary cell line, and this inhibitory effect could not be blocked by inhibitors of phosphatidyl inositol 3 kinase (PI3K) (wortmannin and LY294002) or MAPK (PD098059). In contrast, Niiori- Onishi et al (1999), also using MtT/S cells, reported that IGF-I suppressed luciferase activity driven by a hGH gene promoter, where this action could be blocked by treatment with wortmannin. These divergent results demonstrate that regulation of the endogenous gene vs reporter gene activity may be very different even in the same cell type.…”
Section: Direct Effects Of Igf-i and Insulinmentioning
confidence: 91%
“…These cells closely resemble primary pituitary somatotrophs, as their GH secretion is stimulated by growth hormone releasing hormone (GHRH) and inhibited by IGF-1 (31,33). The effect of IGF-1 treatment on the expression of GH mRNA levels was determined using quantitative RT-PCR (qRT-PCR) in both a concentration-dependent experiment for a 24-h treatment period and a time-dependent experiment with a constant IGF-1 concentration for up to 72 h. Figure 1A illustrates maximal suppression of GH mRNA at an IGF-1 concentration of 30 nM (P Ͻ 0.05) after 24 h. Subsequently, the effect of IGF-1 inhibition of GH mRNA expression relative to the 36B4 housekeeping control gene was demonstrated to be time dependent.…”
Section: Igf-1's Effect On the Gh Cbp And Pit-1/pou1f1 Mrna Levelsmentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF-1), which is produced primarily in the liver under the direct influence of GH, has an important role in not only somatic growth and metabolism but also negative feedback of GH release by targeting both the hypothalamus and pituitary (7,22,39,43). Several in vitro studies have demonstrated the ability of IGF-1 to decrease GH gene expression and hormone release (33,40,(52)(53)(54). Furthermore, transgenic animals with perturbations in the GH axis also demonstrate IGF-1's direct and indirect roles in regulation of the somatotroph (27,30,35,49,51).…”
mentioning
confidence: 99%
“…Transcription-promoting activity was assayed using the luciferase reporter system using pGH-Luc, which carries the rat GH promoter region fused with the luciferase reporter gene (Niiori-Onishi et al 1999). COS-1 cells that were 70% confluent were transfected with 1 µg/ml pGH-Luc or with 0·1 µg/ml pGFP-Pit-1 or with both plasmids, using 4·5 µg/ml DOTAP.…”
Section: Transfection and Dna-binding Assays Of The Gfp-pit-1 Fusion mentioning
confidence: 99%